Characterization of n-Jordan multipliers on rings - Abbas Zivari-Kazempour (Journal of Mahani Mathematical Research)
‎Our main result states that every Jordan multiplier $T$ from a commutative ring $\mathcal{R}$ into a faithful $\mathcal{R}$-bimodule $M$ with characteristic different from $2$‎, ‎is a multiplier. ‎We also generalize this result for all $n≥ 2$ with a suitable condition‎. ‎Furthermore‎, ‎we investigate some illuminating properties of such maps‎. ‎